Recent Advance in Tumor Microenvironment-Based Stimuli-Responsive Nanoscale Drug Delivery and Imaging Platform - Cui, Fengzhi; Liu, Jianhua; Pang, Siwen; Li, Bo (Frontiers in Pharmacology, 2022)
Tumor microenvironment (TME) plays an important role in development, progression and metastasis of cancer, and the extremely crucial feature is hypoxic and acidic. The composition of TME contributes to tumor diversity, and cancer-associated fibroblasts (CAFs), extracellular matrix (ECM), mesenchymal cells, blood vessels and interstitial fluid are the hallmark traits of TME. As the nanotechnology briskly boomed, the nanoscale drug delivery and imaging platform (NDDIP) emerged and has attracted intensive attention. Based on mainly characteristics of TME, NDDIP can be classified into pH-sensitive delivery and imaging platforms, enzyme-sensitive delivery and imaging platforms, thermo-sensitive delivery and imaging platforms, redox-sensitive delivery and imaging platforms and light-sensitive delivery and imaging platforms. Furthermore, imageology is one of the significant procedures for disease-detection, image-guided drug delivery and efficacy assessment, including magnetic resonance imaging (MRI), computed tomography (CT), ultrasound (US) and fluorescence imaging. Therefore, the stimuli-responsive NDDIP will be a versatile and practicable tumor diagnostic tool. In this review article, we mainly introduce the characteristics of TME and summarize the progress of multitudinous NDDIP as well as their applications.